Residual effect of FYM and fertilizers on soil fertility, productivity and economics of pearl millet (Pennisetum glaucum L.) - KUMAWAT, AMIT; YADAV, R. S.; PAREEK, N. K. (Journal of Soil and Water Conservation, 2018)
A field experiment was conducted during two consecutive rabi and kharif seasons to study the residual effect of FYM and fertilizers on productivity and economics of pearlmillet (Pennisetum glaucum L.) on loamy sand soil at Agronomy Farm, College of Agriculture, Swami Keshwanand Rajasthan Agricultural University, Bikaner. The treatments comprising 9 combinations having 3 levels each of FYM (0 and 10 and 20 t ha-1) and fertility (0, 40 kg N + 20 kg P2O5 and 80 kg N + 40 kg P2O5 ha-1) applied in mustard as main plots (residual) and application of 3 fertility levels (0, 30 kg N + 15 kg P2O5 and 60 kg N + 30 kg P2O5 ha-1) for pearlmillet as sub plots in split plot design with 3 replications. Addition of FYM @ 20 t ha-1 to preceding mustard crop persisted its residual effect significantly in increasing the plant height, earhead length, grain weight earhead-1, effective tillers plant-1, grain and stover yield of succeeding pearlmillet over control and 10 t FYM ha-1. Significantly maximum net returns (Rs. 70736 ha-1) with B:C ratio (2.62) of pearlmillet was obtained under 20 t FYM ha-1. Build up in organic carbon, available N, P2O5 and K2O status of soil after of pearlmillet was significantly higher with increasing rates of FYM applied to mustard as compared to other treatments. Increasing levels of fertility in mustard up to 60 kg N + 30 kg P2O5 ha-1 significantly increased plant height, earhead length, grain weight earhead-1, effective tillers plant-1, grain and stover yield, available N, P2O5 and K2O status of soil after of pearlmillet, net returns (Rs. 80426 ha-1) and B:C ratio (3.32) over control.